Di realtà e di possibilità. Una lettura della Postilla conclusiva non scientifica alle “Briciole filosofiche” di Søren Kierkegaard - Germano, Nicolò (Filosofia Morale/Moral Philosophy, 2024)
This contribution aims to outline a history of the evolution of the Kierkegaardian interpretation of the modal category of “possible”, to underline its ethical implications. In particular, what this essay sets out to do is to highlight the importance that “reality” assumes in the categorisation of the modality especially in the Postscript. In order to do so, the different semanticisation of the possible to which Climacus aspires in the Crumbs will be investigated. The new “possible” presented in the work of 1846, in particular, allows us to re-evaluate the position of the ethical stage, which takes on a new depth, and precisely thanks to the theory of possibility presented there allowing the transition to a “second ethics”.